Dermatoscopy-guided therapy of pigmented basal cell carcinoma with imiquimod - Husein Husein-ElAhmed; Maria Antonia Fernandez-Pugnaire (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Dermatoscopy is a non-invasive diagnostic tool used to examine skin lesions with an optical magnification. It has been suggested as a useful tool for monitoring therapeutic response in lentigo maligna patients treated with imiquimod. OBJECTIVE: To examine the accuracy of dermatoscopy as a tool to monitor the therapeutic response of pigmented basal cell carcinoma treated with imiquimod. METHOD: The authors designed a prospective study. Patients with pigmented basal cell carcinoma were included and data regarding the dermatoscopy features were collected following the Menzies criteria, prior to initiating the imiquimod treatment. Subsequent dermatoscopic evaluations were performed at weeks 4 and 8, following imiquimod discontinuation. RESULTS: Twenty lesions were included. The most common pigmented dermatoscopy features were large blue-grey ovoid nests (80%), followed by blue-grey globules (50%) and leaf-like areas (30%). No spoke wheel areas were observed. In 17 out of 20 patients, a response was noted during the first evaluation at 4 weeks, while the clearance was noted at the second check-up after 8 weeks. In two patients, the clearance was found at the initial evaluation at 4 weeks, while in one patient, the response remained unchanged. Blue-grey globules were the fastest to exhibit clearance (50% at week 4), followed by leaf-like areas (15%) and large blue-grey ovoid nests (6.25%). CONCLUSION: According to our results, dermatoscopic evaluation enhances the accuracy in the assessment of the clinical response to imiquimod in pigmented basal cell carcinoma.